Strength and energy dissipation of timber shear walls subjected to arbitrary deformation history study on fatigue behavior of timber structures subjected to repeated earthquake motions: Part 1 - Yoshihiro Yamazaki; Kengo Kanda; Hiroyasu Sakata (Japan Architectural Review, 2020)
Abstract Repeated cyclic loading is thought to decrease the force and deformation capacity of timber shear walls due to the fatigue behavior. This study evaluates the strength and energy dissipation of two typical timber shear walls subjected to various deformation histories to develop a response spectrum method considering the fatigue behavior. Static loading tests and shaking table tests were conducted to observe the performance deterioration. Finally, evaluation formulae for strength and equivalent damping ratio were proposed. The formulae could predict the test results with acceptable accuracy.